Platinum and palladium-hydrogen - Lewis, F.A.; Kandasamy, K.; Tong, X.Q. (Scitec Publications Ltd.,Zurich, Switzerland, 2000)
Platinum and palladium-hydrogen was discussed. Comparison between these two was presented in terms of physical properties, structural characteristics and estimation solubilities. Measurement techniques used to determine diffusion coefficient of hydrogen in platinum and palladium were also listed. Studies revealed formation of hydrogen blisters in platinum and platinum-palladium alloys due to the high pressure of gaseous hydrogen within the voids. Time dependent incremental changes of hydrogen gas pressure in palladium-platinum alloys was also observed during initial removal of hydrogen from the alloy surface.